Undergraduate scientific production in nursing (1997 to 2004): a critical analysis - Kelly Graziani Giacchero; Adriana Inocenti Miasso (Universidade Federal de Goias, 2006)
This study aims to identify the profile of undergraduate scientific production in nursing presented at the University of São Paulo Scientific Initiation Symposia (SIICUSP) between 1997 and 2004, to describe factors that can influence the profile of this production and to make a comparison with the study by PEREIRA et al (1999), which studied the same event between 1993 and 1996. The methodology was based on the analysis of nursing abstracts in SIICUSP proceedings during the studied period, which were classified according to research types, addressed themes, funding agencies and institutions/departments of origin. We identified that most studies were funded by agencies, that non-experimental research predominated and that sociocultural aspects stood out among the research themes. Public institutions provided the greatest contribution to scientific knowledge production. These characteristics are similar to those found by Pereira et al (1999) between 1993 and 1996. The comparative analysis between the production from 1997 and 2004 and PEREIRA et al's results (1999) also revealed a progressive rise in the number of presented studies, as well as the increasing participation of other colleges in SIICUSP (restricted to USP until 1996). Scientific initiation is an important step in research training and a space to develop a knowledge consumption and production culture. Attention is fundamental to avoid scientific initiation from moving away from current society's needs and from the subjects that motivate students, with a view to guaranteeing the growth, quality and valuation of nursing knowledge production.